Location of river cargo ports on the Odra Waterway - the results of the analyzes Szczecin and Świnoujście Seaports Authority - Bogusz Wiśnicki; Dorota Dybkowska-Stefek; Łukasz Kolanda; Justyna Relisko-Rybak (Przegląd Komunikacyjny)
Studies on the location of river ports along the Odra Waterway (ODW), the Silesian Canal and the Polish section of the Danube-Odra-Elbe Canal (DOL) have been completed. The multi-criteria analysis of the transport and economic potential of the ODW allowed to determine the location of transport nodes and river ports and to define their categories. The indicated river ports should constitute future concentration points for transport and logistics services. This is especially important in the context of the update of the European TEN-T network, which is planned for 2023. Hence, the key recommendations relate to nine new international transport nodes and trimodal ports located therein. Keywords: River ports; Transport nodes; Cargo port